Behaviour of Eccentric Concrete Columns Reinforced with Carbon Fibre-Reinforced Polymer Bars - Zrar Sedeeq Othman; Ahmed Heidayet Mohammad (Advances in Civil Engineering)
The use of steel bars as reinforcement is not preferred in some concrete structures because steel causes corrosion or electric magnetic field problems. One of the best alternatives to steel bars is carbon fibre-reinforced polymer (CFRP) bars. The experimental program consisted of 18 reinforced rectangular concrete columns under different eccentric loadings. Out of the 18 columns, 15 were reinforced with CFRP longitudinal rebars and ties and 3 were reinforced with conventional steel rebars and ties as reference columns. The following parameters were included in this study: the replacement of steel with CFRP bars, eccentricity of load, longitudinal reinforcement ratios, and tie spacing. Test results in terms of load-strain, load-mid height deflection curves, and crack patterns showed that the column reinforced with CFRP bars behaved similarly to the concrete column reinforced with conventional steel bars with a slight difference in axial and flexural capacity. The increment in CFRP longitudinal reinforcement ratios from 1.4% to 2.0% and 3.6% reasonably increased the maximum carrying capacity for different eccentricities used herein. The axial ratios of experimental to theoretical results (PExp./PTheor.) were determined for specimens in the present work and those from previous studies to assess the efficiency of the theoretical models.